THE SPECTRUM OF GENETIC DEFECTS IN CHRONIC LYMPHOCYTIC LEUKEMIA - Davide Rossi; Marco Fangazio; Gianluca Gaidano (Mediterranean Journal of Hematology and Infectious Diseases)
Chronic lymphocytic leukemia (CLL) is the most common leukemia in the Western world and shows a remarkable heterogeneity in the clinical course. Understand the genetic basis of CLL may help in clarifying the molecular bases of this clinical heterogeneity. Recurrent chromosomal aberrations at 13q14, 12q, 11q22-q23 and 17p13, and TP53 mutations are the first genetic lesions identified as drivers of the disease. While some of these lesions are associated with poor outcome (17p13 deletion, TP53 mutations and, to a lesser extent, 11q22-q23 deletion) others are linked to a favorable course (13q14 deletion as sole aberration). Recently, next generation sequencing has revealed additional recurrent alterations in CLL targeting the NOTCH1, SF3B1, and BIRC3 genes. NOTCH1, SF3B1, and BIRC3 lesions provide: i) new insights on the mechanisms of leukemogenesis, tumor progression and chemoresistance in this leukemia; ii) new biomarkers for the identification of poor risk patients, having individually shown correlations with survival in CLL; and iii) new therapeutic targets, especially in the setting of high risk disease. This review will summarize the most important genetic aberrations in CLL and how our improved knowledge of the genome of leukemic cells may translate into improved patients' management.